Causes of female infertility by Diagnostic Laproscopy - Tomar, Surabhi; Parmar, Meenal; Pradhan, Aritra (International Journal of Medical Research and Review, 2014)
Objective: To evaluate the causes of primary female infertility with diagnostic laproscopy. Study Design: This study is a case series. Place and Duration of Study: The study has been carried out in Obstetric and Gynaecology department in National Institute of Medical Sciences (NIMS) College and Hospital, Jaipur,, Rajasthan, from September 2013 to July 2014. The tubal patency was tested by chromopertubation using methylene blue dye. Methodology: Inclusion criteria include all primary infertile females who underwent diagnostic laparoscopy during the study period & Normal pelvic examination. Couples who had not lived together for at least one year & Women with medical disorders and contraindications for laproscopic surgery were excluded from study. Results: Out of 100 primary infertility women, mean age of infertility was 27.5 years. Maximum number of patient’s presented with infertility of duration less than six years. 43% had tubal blockage as the most common finding which was followed by pelvic adhesions. Bilateral tubal block was diagnosed maximum by laproscopy and HSG combined i.e. 40% followed by laprosopy alone in 32% cases. Conclusion: Most common causes responsible for primary infertility in women were tubal occlusion, peritubal and periovarian adhesions and endometriosis.